3D-PHARMACOPHORE MODELING AND MOLECULAR DOCKING TO STUDY THE POTENTIAL ANTI-CANCER AGENT FROM Ficus septica Burm. L - Asman Sadino; Benny Permana; Meilia Suherman; Fuji Ayu Noviartika (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Perjuangan Tasikmalaya, 2022)
In vitro testing showed that awar awar (Ficus septica Burm. L ) leaf had an anticancer activity. Ethanol extract from awar-awar leaves could selectively inhibit cancer cell growth with IC50 values, there were MCF7 breast cancer cells (48 µg/ml), HeLa cervical cancer cells (122.4 µg/mL), and WiDR cancer cells (75.9 µg/mL). However, the active compounds that play a role in inhibiting the three cancer cells are not yet found. Therefore, this research carried out to find out the active compound using in silico. 3D-pharmacophore modeling and Molecular docking were developed for finding out the potential compound that could be acted as an anti-cancer agent. Screening pharmacophore was performed using LigandScout® 4.4 software for searching the matching pharmacophore features against chemical structure databases. Docking was performed using Autodock Tools® and visualized using Discovery Studio Visualizer® software to see the ligand interaction with the active binding site at the receptor and continue with ADMET properties to evaluating the Pharmacodynamic activities of the Hit compounds. Among 17 types of compounds tested, 11 compounds showed anticancer activity and genistin was found promising and showed potential inhibitory characteristics as an anticancer compared to other active compounds of awar-awar leaves. This study suggests that these compound could be used as a lead compound for anticancer agents.